Between Patient-Hood And Trust: Interlocking Doctor-Patient Relationship Among Mental Health Care Users In Kedah And Pulau Pinang - Kamarunzaman, Nur Zafifa; Selamat, Nor Hafizah (2016)
The article aims at exploring the trust establishment among patients with depression during their journey to psychiatric patient-hood. This study was undertaken in government hospital involving 29 psychiatric outpatient users in Kedah and Pulau Pinang respectively. Phenomenology study and gender lens employed to scrutinize on the patients’ lived experiences in mental health care, at the same time magnifying the gender differences in perceiving the service. Semi-structured in-depth interview and non-participant observation were the tools used in data collection. The data then explicated with the aid of a qualitative data analysis tool, Atlas.ti., version 7.5. Through the findings, the study identified “Trust” appears critical in the accounts of the patients in shaping the doctor-patient relationship; with at least five interlocking sub-themes describing the health professional’s characteristic while giving the service. The sub-themes include doctor’s integrity, concern, competencies, empathy, and autonomy enabler. There are no gender differences detected in most of the sub-themes, except for doctor’s competency, and integrity. Barriers in language and communicating with patients cultural believe potentially moving away from the patients’ interest elsewhere for help seeking or diminishing the client’s compliance. The findings are consistent with previous studies whereby language and lacking in a cultural competence garner gender stereotype in treatment giving. Thus, trust in this context becomes the enabling or disabling factor for the patient to stay on in the treatment.